Strategic Leadership and Risk Management of Institutional Administrators under Vocational Education in the Southern Border Provinces - Sriyota, Matee (Al-HIKMAH Journal, 2022)
This research purposes were to 1) study the level of strategic leadership of institutional administrators under vocational education in the southern border provinces.; 2) study the level of risk management of institutional administrators under vocational education in the southern border provinces.; 3) compare the strategic leadership of the institutional administrators under vocational education in the southern border provinces classified by gender, position, and work experience.; 4) compare risk management of institutional administrators under vocational education in the southern border provinces classified by gender, position, and work experience.; 5) study the relation between strategic leadership and risk management of institutional administrators under vocational education in the southern border provinces.; 6) compile recommendations on strategic leadership and risk management of institutional administrators under vocational education in the southern border provinces. The samples were 300 teachers and school administrators, calculated using the Krejcie and Morgan formulas. Data analysis used the statistics as frequency, percentage, average, standard derivation, T-Test, F-Test, and Pearson product moment correlation was applied. As the consequences: The overall strategic leadership of educational institution administrators under vocational education in the southern border provinces is at a high level. The overall risk management of educational institution administrators under vocational education in the southern border provinces is at a high level. Comparison of strategic leadership level of educational institution administrators under vocational education in the southern border provinces, classified by gender, position, and work experience were statistically significantly different at the .01 level. Comparing the level of risk management of educational institution administrators under vocational education in the southern border provinces, classified by gender, position, and work experience has no difference but the position was significantly different at the .01 level. Relation between strategic leadership and risk management of school administrators under vocational education in the southern border provinces was a statistically significant positive correlation with risk management at the .01 level, with a high correlation across all aspects. Suggestions for strategic leadership and risk management of school administrators under the vocational education in the southern border provinces, indicated that the administrators must plan, monitor, and determine the vision by the policy to promote culture in the organization. In addition, the good governance is applied in administrating system with the participation of staffs in undertaking any task, illustrating how learning experience creates faith, accuracy in the educational institutes to allow and bringing the new technology into the educational institute efficiently.